2015
DOI: 10.1038/ncomms6917
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids mediate induction of microRNA-708 to suppress ovarian cancer metastasis through targeting Rap1B

Abstract: Glucocorticoids are widely used in conjunction with chemotherapy for ovarian cancer to prevent hypersensitivity reactions. Here we reveal a novel role for glucocorticoids in the inhibition of ovarian cancer metastasis. Glucocorticoid treatments induce the expression of miR-708, leading to the suppression of Rap1B, which result in the reduction of integrin-mediated focal adhesion formation, inhibition of ovarian cancer cell migration/invasion and impaired abdominal metastasis in an orthotopic xenograft mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 43 publications
(56 reference statements)
13
108
1
Order By: Relevance
“…The A2b-Epac1-Rap1B Pathway in the Context of Migration of Cancer Cells-Our discovery of a critical involvement of Rap1B in the positioning of the centrosome and nucleus may explain previous observations that cells isolated from Rap1B-deficient mice display decreased migration (80), that Rap1B knockdown results in impaired cell migration of human endothelial cells (81), and that Rap1B suppression by miR-708 results in inhibition of ovarian cancer cell migration/invasion (83). However, some studies reported a correlation between hypoxia and cell motility in cancer cells, including enhanced metastatic potential (84,85).…”
Section: Discussionmentioning
confidence: 97%
“…The A2b-Epac1-Rap1B Pathway in the Context of Migration of Cancer Cells-Our discovery of a critical involvement of Rap1B in the positioning of the centrosome and nucleus may explain previous observations that cells isolated from Rap1B-deficient mice display decreased migration (80), that Rap1B knockdown results in impaired cell migration of human endothelial cells (81), and that Rap1B suppression by miR-708 results in inhibition of ovarian cancer cell migration/invasion (83). However, some studies reported a correlation between hypoxia and cell motility in cancer cells, including enhanced metastatic potential (84,85).…”
Section: Discussionmentioning
confidence: 97%
“…The number and size of tumor nodules in the peritoneal cavity as well as the volume of ascites fluid were reduced with transfectants in comparison to the control cell line (79). (86). GC are used in conjunction with chemotherapy of EOC to prevent hypersensitivity reactions (87).…”
Section: Mir-138mentioning
confidence: 99%
“…GC are used in conjunction with chemotherapy of EOC to prevent hypersensitivity reactions (87). miR-708 is down-regulated in metastatic OVC and patients with high miR-708 expression show significantly better survival (86). miR-708 inhibits migration and invasion of EOC cell lines as shown by wound healing and transwell Boyden chamber assays (86).…”
Section: Mir-138mentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer is one of the most frequent malignancies of the female reproductive system, with an incidence rate of ~3% (1), and is the sixth most common type of cancer in women (2). However, the mortality rate associated with ovarian cancer is the highest of the gynecological malignancies.…”
Section: Introductionmentioning
confidence: 99%